Effect of a mindfulness-based pilot intervention on maternal-fetal bonding - Shreffler KM; Tiemeyer S; Ciciolla L; Croff JM (Dove Medical Press, 2019)
Karina M Shreffler,1 Stacy Tiemeyer,1 Lucia Ciciolla,2 Julie M Croff31Department of Human Development and Family Science, Oklahoma State University, Stillwater, OK, USA; 2Department of Psychology, Oklahoma State University, Stillwater, OK, USA; 3Department of Rural Health, Center for Health Sciences, Oklahoma State University, Tulsa, OK, USAAbstract: This pilot study explored the effects of a two-week mindfulness-based intervention designed to enhance maternal-fetal bonding among pregnant women. Participants who listened to their baby’s heartbeat every day for two weeks and received four texts per week with mindfulness-based activities to do from home reported a significant increase in reported maternal-fetal attachment scores across the study period. Enhancing maternal-fetal bonding through this low-cost intervention has the potential for reducing adverse birth outcomes.Keywords: pregnancy, mindfulness, intervention, attachment, bonding, MFAS